The execution of independent work in teacher training (Revision) (REDEL. Revista Granmense de Desarrollo Local, 2021)
The objectives declared in the UNESCO 2030 agenda in education include raising the quality of this process, to which Higher Education is no stranger in the search for professionals increasingly committed to the changes that occur in society contemporary. Consequently the independent work of the students contributes to the gradual increase in the level of cognitive independence, which requires a developmental conception that starts from the change of position between teachers and students, gradually increasing the degree of complexity of the tasks, as well as teaching reasoning and study according to the professional preparation of future teachers. In this way, a didactic model of independent work management is introduced and the subsystem related to its execution is characterized. To achieve the proposed objective, modeling and the structural systemic approach were fundamentally used as theoretical methods.Keywords: independent work, conception of independent work, developmental teaching, genitive independence.
Keywords: independent work, conception of independent work, developmental teaching, genitive independence